SCENARIO PLANNING TO DEVELOP BUSINESS EXPANSION STRATEGIES IN THE SKINCARE INDUSTRY - Nurjihan Khairunisa; Yos Sunitiyoso (Jurnal Ekonomi, 2023)
The Indonesian skincare market is projected to grow at a CAGR of 8.9% from 2021 to 2026, with SMEs accounting for the majority of companies. PT XYZ plans to enter the market and increase its market share and profitability through product diversification. This study used scenario planning and qualitative research with 10 diverse stakeholders to explore strategies for business expansion in the skincare industry at PT XYZ. The results indicate that demand and technology are the most significant uncertainties influencing the market. The study offers recommendations for dealing with these uncertainties and implementing strategies in the future.